Evaluation and comparison of the collection of selected PAASCU level II accredited high school libraries in Quezon City through collection mapping and its implications in collection development - Macrohon, Denise Marie O.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
Nowadays, school libraries and media centers are becoming more relevant. Thus, it is important to maintain a quality collection to support the school's mission, vision, and goals. School librarians must find ways to evaluate the collection to ensure that the best materials may be delivered effectively to the users.
This study examined and evaluated the printed book collection of two selected PAASCU Level II accredited high school libraries in Quezon City. Collection mapping was used as an evaluation technique to show the graphic representation of a library collection's strengths and weaknesses. The curricula of the Claret School of School of Quezon City and School of Saint Anthony Quezon City, the shelf list of their respective library and media centers, curriculum mapping forms, and interviews with the library staff were used as research instruments.
Findings revealed that out of 8,326 books from Claret School, 3,781 books or 45.42% were categorized as academic books or books that are necessary to support the school's curricular offerings. There were 3,360 books were published within the last 20 years, between 1995 and 2014. Claret School has a strong English (652 books) and Math (652 books) book collection but has a relatively weak Filipino (408 books) and Math (433 books) book collection. The school also has a strong collection in English Literature (256 books), Philippine History (214 books), and English Grammar and Composition (211 books) and a weak collection in Statistics and Probability (41 books), Geometry (59 books), and General Social Science (59 books).
On the other hand, out of 11,019 books from School of Saint Anthony, 4,347 books or 39.46% were categorized as academic books. There were 1,704 books published within the last 20 years, between 1995 and 2014. School of Saint Anthony has a strong Social Science (1020 books) and Math (783 books) book collection but has a relatively weak Filipino (174 books) and English (347 books) book collection.
The school also has a strong collection in Algebra (304 books), Philippine History (267 books), and World History (267 books) and a weak collection in Filipino Communication (25 books), Trigonometry and/or Calculus (49 books), and Chemistry (51 books). Despite having the same PAASCU accreditation level, the printed book collections of Claret School and School of St. Anthony differ both in currency and the amount of books per subject area. Based from the findings of the study, it was shown that collection mapping is a good evaluation tool to assess the adequacy and quality of a school's library collection.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Collection development (Libraries) -- Philippines -- Quezon City; High school libraries -- Philippines -- Quezon City -- Evaluation; Database design -- Philippines -- Quezon City